Twisting gating residues in the Orai pore. (January 2021) - Bonhenry, Daniel; Schober, Romana; Schindl, Rainer
Graphical abstract: Abstract: The store-operated calcium channels Orai1−3 form extraordinary long and funnel like pores, in stark contrast to a classical pore loop architecture. A hydrophobic segment centrally located in the Orai pore controls gating. Here, we comment on a recent work that describes decisive binding between three residues that controls the open and closed conformation of Orai channels.